TANTANGAN PRODUKSI PERTANIAN TERHADAP KELANGKAAN AIR DAN KETERSEDIAAN LAHAN PERTANIAN DI MASA DEPAN - Sihombing, Vista; Siadari, Ulidesi (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2023)
This research aims to analyze the challenges of future agricultural production in terms of water scarcity and the availability of agricultural land while exploring strategies that can be applied to address these challenges. The study employs a systematic literature review approach with a sample of 30 journals from various developed and developing countries. These journals span publication years from 2000 to 2021. Further investigation by reading the abstracts of each selected journal was conducted to ensure their relevance to the research objectives. The research findings indicate that water scarcity and the availability of agricultural land are significant factors influencing the sustainability of agricultural production. The absence of these inputs can have a substantial impact on meeting global demand. Factors such as extreme climate change, land conversion, population growth, and increased demand for agricultural products contribute to water scarcity and the limited availability of agricultural land. Strategies employed to address these issues involve a combination of policy measures and environmental prevention and adaptation strategies, such as wastewater and saline water management for irrigation, the use of superior crop varieties, changes in crop intensity, improved weather forecasting for farmers, and crop diversification. Moreover, to combat the shrinking availability of agricultural land, several strategies can be implemented, including optimizing land-use intensity, increasing the crop yield index, and formulating policies related to land-use conversion. Kata kunci: kelangkaan air, lahan pertanian, produksi pertanian,